Binding activity of Valeriana fauriei root extract on GABAA receptor flunitrazepam sites and distribution of its active ingredients in the brain of mice – A comparison with that of V. officinalis root. (5th October 2021) - Ota, Misato; Ni, Hao; Maki, Yasuhito; Kato, Daiki; Moriguchi, Shohei; Nakayama, Shuto; Oiwa, Yuki; Ishiuchi, Kan'ichiro; Makino, Toshiaki
Abstract: Ethnopharmacological relevance: Valeriana fauriei root (VF) is a crude drug registered in the Japanese Pharmacopeia 17th Edition and a known substitute for V. officinalis (VO). Although VO has been pharmacologically evaluated for its sedative effects and mechanism of action, data regarding VF remain scarce. Aim of the study: We compared the binding affinity of VF and VO extracts, as well as examined the active ingredients in the VF extract, on flunitrazepam sites of γ-aminobutyric acid receptor type A (GABAA receptor). Furthermore, we confirmed whether these active ingredients were distributed in the brain of mice orally administered the VF extract. Materials and methods: We prepared the assay system to evaluate the binding activity of flunitrazepam sites of GABAA receptor using a 96-well plate and assessed the activities of VF and VO extracts. We then analyzed their constituents using HPLC with principal component analysis (PCA) and evaluated active ingredients correlated with their activities. The distribution of active ingredients in the plasma and brain of mice orally administered the VF extract prepared with different emulsifiers were analyzed by LC-MS/MS. Results: The ethanol extract of VF exhibited significantly higher activity on flunitrazepam sites of GABAA receptor than VO. For the VF extract, kessyl glycol diacetate (KGD) was markedly associated with the binding activities; however, active ingredients included KGD, kessyl glycol 8-acetate (KG8), α-kessyl acetate (α-KA), and coniferyl isovalerate (CI). For VO, valerenic acid and five other compounds were associated with the binding affinity on flunitrazepam sites of GABAA receptor. On emulsifying the VF extract with a fat-soluble glycerin fatty acid ester, the plasma and brain distributions of KGD tended to be higher, those of KG8 were significantly more than 10-times higher, and those of α-KA was lower than those of the VF extract emulsified with water-soluble gum arabic, after oral administration in mice. Conclusions: Based on the binding activity on flunitrazepam sites of GABAA receptor and brain distribution, KGD, KG8, and α-KA can be considered active ingredients of VF. The addition of a fat-soluble emulsifier promoted the absorption of KGD, the main active ingredient, and KGD was metabolized to KG8 in the body. The present results suggest a possible mechanism underlying the sedative effect for VF, and these three compounds can be used as marker compounds to evaluate the quality of VF products. Graphical abstract: Image 1